2016
DOI: 10.1597/14-003
|View full text |Cite
|
Sign up to set email alerts
|

Weight, Length, and Body Mass Index Growth of Children under 2 Years of Age with Cleft Lip and Palate

Abstract: Children with CLP/ICP had impaired W/A and BMI growth with spontaneous recovery starting early in childhood. This study established specific W/A, BMI, and L/A growth curves for children with cleft lip and palate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
32
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 21 publications
5
32
0
8
Order By: Relevance
“…Malnutrition is a characteristic feature of CL/P (6,7). The growth pattern of the majority of patients with CL/P appears to be markedly abnormal, while some patients still follow a relatively normal pattern of weight and length acquisition (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malnutrition is a characteristic feature of CL/P (6,7). The growth pattern of the majority of patients with CL/P appears to be markedly abnormal, while some patients still follow a relatively normal pattern of weight and length acquisition (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the majority of our understanding of malnutrition and developmental delay in infants with CL/P has been acquired over the past 10 years (8)(9)(10)(11). Very little novel statistical data regarding the true development status of infants with CL/P has been published, with the exception of the studies from and Prahl et al (12) and Miranda et al (7). There is an urgent need for a large case statistical investigation of malnutrition and developmental delay in infants with CL/P in other districts and nations, especially in China.…”
Section: Introductionmentioning
confidence: 99%
“…At the time of primary palate surgery, prevalence of FTT was 20% in ICP infants but had increased from 14% to 23% in UCLP infants and slightly decreased from 28% to 22% in BCLP infants. FTT prevalence was higher in syndromic than non-syndromic cleft infants (33% and 5% in syndomic and non-syndromic ICP infants respectively at the time of lip surgery) Miranda et al (2016). andTabari et al (2015) reported that 4.1% and 5% respectively of cleft palate with or without cleft lip infants had weight-for-age values above the 95 th percentile, suggesting that some CP±L children could be overweight.…”
mentioning
confidence: 98%
“…Miranda et al, 2016;Cubitt et al, 2012). The severity of undernutition in cleft infants is linked to the cleft type and the occurrence of other anomalies or syndromes with CLP and ICP infants being more undernourished compared to ICL infants(Miranda et al, 2016;Cubitt et al, 2012;Beaumont et al, 2008;Montagnoli et al, 2005)…”
mentioning
confidence: 99%
See 1 more Smart Citation